Spiritual Heritage of Europe in the Light of Personalistic Universalism of Karol Wojtyla—John Paul II - Arkadiusz Modrzejewski (Religions, 2021)
The article is devoted to the philosophical and theological thought of Karol Wojtyła, i.e., John Paul II, who in his considerations gave a lot of attention to European issues, including the spiritual heritage of Europe, to European Christianity in its two varieties, i.e., Latin and Byzantine, and to the relationship between European unity and the pluralism of national cultures. We discover the proper sense of Wojtyła’s European thought by referring to his inspiration with the theology of spirituality, which was the future Pope’s first research experience. His vision of Europe is based on personalistic philosophy, thanks to which these considerations take a universal form. The key to understanding universalism is personalistic hermeneutics, owing to which we perceive the source of universality in man understood as a person. However, Wojtyła’s universalism has two faces. It is universalism in the literal sense, thanks to the personalistic perspective. In the axiological layer it also takes the form of Christian or European and in a way also Eurocentric universalism, which is related to the perception of Europe as a depositary and promoter of universal values of Christianity.